PCSK-9 inhibitors: a new direction for the future treatment of ischemic stroke - Zhou, Lin; Zhang, Hongyu; Wang, Shuyi; Zhao, Hong; Li, Yongnan; Han, Juqian; Zhang, Hongxu; Li, Xiaoyuan; Qu, Zhengyi (Frontiers in Pharmacology, 2024)
Ischemic stroke, the most prevalent and serious manifestation of cerebrovascular disease, is the main cause of neurological problems that require hospitalization, resulting in disability and death worldwide. Currently, clinical practice focuses on the effective management of blood lipids as a crucial approach to preventing and treating ischemic stroke. In recent years, a great breakthrough in ischemic stroke treatment has been witnessed with the emergence and use of a novel lipid-lowering medication, Proprotein convertase subtilisin kexin type 9 (PCSK9) inhibitor. And its remarkable potential for reducing the occurrence of ischemic stroke is being acknowledged. This article aims to provide a comprehensive review, encompassing the association between PCSK9 and the heightened risk of ischemic stroke, the mechanisms, and the extensive evidence supporting the proven efficacy of PCSK9 inhibitors in clinical practice.Through this present study, we can gain deeper insights into the utilization and impact of PCSK9 inhibitors in treating ischemic stroke.